DAYA TARIK WISATA NEGERI AMAHUSU DALAM UPAYA PENGEMBANGAN DESTINASI PARIWISATA BERBASIS MASYARAKAT - Latupeirissa, Grasyeli; Sudiarta, I Nyoman; Pakniany, Yamres (Institut Teknologi dan Bisnis Kristen Bukit Pengharapan, 2023)
This study aims to explore the tourism potential in Negeri Amahusu. Even though it has abundant potential, there is one natural tourist attraction in the form of beach tourism, which has not yet been used as a destination. Several historical/cultural tourist attractions are also currently it has not been used as tourist destinations. Even the local government lack of role sees these tourist attractions and related to the community has minimal awareness of the development of these tourist destinations. Based on the explanations that have been presented, the authors conducted research with the formulation of the problem, namely; 1) What are the potentials in Negeri Amahusu in terms of natural tourism potential in the form of beach tourism, cultural tourism, culinary tourism, historical tourism or religious tourism, to develop community-based tourism destinations, 2) What are the efforts or strategies made by the government and community in the development of community-based tourism destinations. This research was conducted using qualitative research methods, using data collection techniques in the form of interviews with several informants from both the Negeri Amahusu and the Ambon City, in this case, the Ambon City Tourism and Culture Office and the local community. The study results show that there are natural tourist attractions in the form of beach tourism and historical tourist attractions which until now have not been used as tourist destinations until now. There is a lack of attention from the local government regarding this matter and the lack of public understanding related to the existing tourism potential in developing this tourism.